KONDISI SUMUR DAN PEMODELAN ARAH ALIRAN AIRTANAH BEBAS PADA BENTUKLAHAN FLUVIOMARIN DI JAKARTA - Cahyadi Setiawan; Suratman Suratman; Muh Aris Marfa,i (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2016)
ABSTRACT Growing population have an impact on the strategy of fulfillment the water need and degradation of groundwater quality in Jakarta, especially in fluviomarine landforms in Jakarta. The purpose of this study was to determine the condition of wells and create a model of groundwater flow direction on fluviomarine landforms based on the season. Methods in this research study include three main aspects, namely population, characteristics of the object under study, and analysis. The population in this study using 30 groundwater wells sample representative of the population. Relating to the characteristics of the object under study, this study using a survey method. The survey is a sample survey on wells population who still use unconfined groundwater. About data analysis, then in this study used quantitative and qualitative approaches to the modeling of the groundwater flow direction using the Inverse Distance Weighted (IDW) in ArcGIS. The results showed that the unconfined groundwater wells in the study area consisted of dug wells and pantek wells. It is generally known that groundwater levels in the rainy season are higher than the dry season with a depth of groundwater level in the dry season to be deeper than the rainy season. Most of the groundwater level in organic settlements in the study area is below sea level, whereas in planned settlements is rarely found people who use groundwater. The depth of unconfined groundwater well less than 20 m with a thickness of water on the wells in the rainy season are thicker than the dry season. Groundwater flow direction along the north coast of central and western parts likely to lead to the mainland, while the southern part has a groundwater flow that is likely to lead to the North. Keywords: Fluviomarine Landforms In Jakarta; Unconfined Groundwater; Groundwater Flow Direction